1989
DOI: 10.1590/s0074-02761989000100007
|View full text |Cite
|
Sign up to set email alerts
|

Actividad molusquicida del Piquerol A aislado de Piqueria trinervia (compositae) sobre ocho especies de caracoles pulmonados

Abstract: In laboratory trials an aqueous solution of Piquerol A from Piqueria trinervia, collected in several regions of Mexico, showed a molluscicide action on the adults of eight different pulmonates snails species: Fossaria (Fossaria) humilis, F. (Bakerilymnaea) sp., Pseudosuccinea columella and Stagnicola attenuata from Mexico; F. (B.) cubensis and Physa cubensis from Cuba; P. columella and Biomphalaria glabrata from Brazil; B. glabrata from Puerto Rico; and S. elodes from U.S.A. The solution was tested at 50, 25 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Notably, 50 (17%) compounds were found only in mamey apple (e.g., droserone, norlichexanthone, procyanidin C1, 3,4-leucopelargonidin II, and piquerol A). Piquerol A is a sesquiterpene with low stability in nature and has only previously been tested as an insecticide and as an inhibitor of metabolism in cell cultures [22]. About 43 (15%) were tentatively identified only in camapu (e.g., myristicin, 11-deoxocucurbitacin, synapic acid I, and pseudopurpurin).…”
Section: Phytochemical Profile By Uplc-ms Ementioning
confidence: 99%
“…Notably, 50 (17%) compounds were found only in mamey apple (e.g., droserone, norlichexanthone, procyanidin C1, 3,4-leucopelargonidin II, and piquerol A). Piquerol A is a sesquiterpene with low stability in nature and has only previously been tested as an insecticide and as an inhibitor of metabolism in cell cultures [22]. About 43 (15%) were tentatively identified only in camapu (e.g., myristicin, 11-deoxocucurbitacin, synapic acid I, and pseudopurpurin).…”
Section: Phytochemical Profile By Uplc-ms Ementioning
confidence: 99%
“…De la familia Compositae Cruz-Reyes y col. 4 , probaron el jugo proveniente de Piqueria trinervia sobre Lymnaea cubensis de México y Pseudosuccinea columella de Brasil con una elevada mortalidad a las 24 horas sin recuperación, mientras que Alzerreca y col.…”
Section: Concentraciónunclassified
“…Piquerol A, piquerol B, trinervinol, and carquejilo acetate have been isolated from P. trinervia [ 9 ]. Piquerol has been tested as a molluscicidal agent against eight species of pulmonated snails [ 10 ], evaluated for its inhibitory effect on the growth of epimastigotes of Trypanosoma cruzi [ 11 ], and shown to have antimicrobial effects against pathogenic bacteria [ 12 ]. In 2017, Rufino-González et al found that piquerol and trinervinol had anti-giardia effects against Giardia intestinalis [ 13 ]; however, there are no reports about the anti-inflammatory activity of P. trinervia .…”
Section: Introductionmentioning
confidence: 99%